Comparison of arthroscopic single-row and double-row repair in the treatment of rotator cuff tears: A protocol of cohort analysis. Issue 29 (17th July 2020) - Lin, Yanming; Zhao, Jiasong; Qiu, Heng; Huang, Yong
Abstract: Background: Single-row (SR) and double-row (DR) techniques are 2 kinds of widely used approaches for the arthroscopic repair of rotator cuff. This retrospective clinical trial was performed to address the question of whether a DR rotator cuff anchor repair gives results superior to a SR anchor repair in clinical outcome scores and complication rates. Methods: This study was performed and reported in accordance with the Strengthening the Reporting of Observational studies in Epidemiology checklist. We retrospectively reviewed our database, which was collected prospectively. From 2014 to 2017, 264 patients underwent arthroscopic rotator cuff repair by an experienced single shoulder surgeon with the SR and DR techniques. This study was approved by the institutional review board in our hospital and was registered in the Research Registry. Outcome measures included Constant-Murley score, muscle strength, patient satisfaction, passive range of motion, and retear rates. Results: The hypothesis was that the DR technique would achieve better functional scores and fewer complications as compared to the SR technique in treatment of rotator cuff tears.